A rare combined injury of dorsal fracture-dislocation of four carpometacarpal joints and trapezium, trapezoid and distal radius bone fractures - Touloupakis, Georgios; Stuflesser, Wilfried; Antonini, Guido; Ferrara, Fabrizio; Crippa, Cornelio; Lettera, Maria Gabriella (Acta Biomedica Atenei Parmensis, 2016)
Incorrect or delayed diagnosis and treatment of the carpometacarpal fracture-dislocations is often associated with poor prognosis. We present a rare case of unusual pattern of injury, involving dorsal dislocation of four ulnar carpometacarpal joints, associated with fracture of the trapezium, a burst fracture of the trapezoid  bone and an extra-articular fracture of the third distal  of the radius. The first surgical intervention was followed by unsatisfactory results, confirmed by the CT scans. A second surgery followed and an open reduction and pinning with K wires performed. Post-operative follow up lasting for nine months revealed a very good surgical outcome.